Fasting-induced lipolysis and hypothalamic insulin signaling are regulated by neuronal glucosylceramide synthase - Herzer, Silke; Meldner, Sascha; Gröne, Hermann-Josef; Nordström, Viola (Diabetes, 2015)
Central nervous regulation of body weight and adipose tissue function is mainly conducted by hypothalamic neurons. Neuronal function depends on the integrity of the membrane lipid microenvironment. Lipid microdomains contain large quantities of cholesterol and glycosphingolipids, including glucosylceramide synthase (GCS) (gene Ugcg)-derived gangliosides. The current study demonstrates that Ugcgf/f//CamKCreERT2 mice with genetic GCS deletion in forebrain neurons, dominantly targeting mediobasal hypothalamus (MBH), display impaired fasting-induced lipolysis accompanied by a decreased norepinephrine content in white adipose tissue (WAT). MBH insulin receptor (IR) levels and signaling are increased in Ugcgf/f//CamKCreERT2 mice. These results are in concordance with reports stating that MBH insulin signaling restrains sympathetic nervous outflow to WAT in fasted mice. In line with the in vivo data, pharmacological GCS inhibition by Genz123346 also increases IR levels as well as IR phosphorylation in insulin-stimulated hypothalamic cells. In addition to studies suggesting that simple gangliosides like GM3 regulate peripheral IR signaling, this work suggests that complex neuronal gangliosides also modulate hypothalamic IR signaling and protein levels. For example, the complex ganglioside GD1a interacts dynamically with the IRs on adult hypothalamic neurons. In summary, our results suggest that neuronal GCS expression modulates MBH insulin signaling and WAT function in fasted mice.
Gesehen am 31.08.2020